Adaptação transcultural e avaliação das propriedades psicométricas de escalas de sintomas e cognições pós-traumáticas em crianças e adolescentes - Lobo, Beatriz de Oliveira Meneguelo (2014)
Exposure to potentially traumatic events in childhood and adolescence has been reported in approximately 50 % of children and adolescents. Symptoms as anxiety, depression, suicidal behavior, inappropriate sexual behavior and Posttraumatic Stress Disorder has been observed in traumatic exposed youth. Previous literature indicates that cognitive processing is related to the development, maintenance and aggravation of posttraumatic symptoms. Considering the variability of responses related to the traumatic events exposure in childhood and adolescence, early psychological is critical to the establishment of appropriate interventions. This dissertation consists of three empirical studies presented in the form of articles. The overall objective of this study was to conduct a cross-cultural adaptation and evaluate the psychometric properties of the Trauma Symptom Checklist for Children (TSCC) and the Child Posttraumatic Cognitions Inventory (CPTCI). The TSCC (Study 1) was properly adapted and demonstrated adequate internal consistency. The PCA yielded a six-factor solution, as proposed in the TSCC original structure. CFA was conducted to examine fit of the TSCC original six-factor solution. For all clinical scales (excepted Anger), were explored alternative models removing items that had a low correlation with other TSCC items and the latent construct. Despite rising rates of model fit, this study does not suggest changes in the structure of TSCC, considering that these are preliminary results of TSCC psychometric properties on a Brazilian sample. Good evidences of convergent validity were evidenced through correlations with the CDI and CBCL. Study 2 showed an adequate cross-cultural adaptation and content validation of CPTCI. The results of Study 3 showed high internal consistency and a two-component solution ( Permanent and disturbing change and Fragile person in a scary world ), Despite the similarity with the original structure of CPTCI, CFA showed that the original model did not fit well the data. Convergent validity evidences were obtained through correlations with TSCC and CDI. Findings highlighted by the three studies suggest that the TSCC and CPTCI are reliable and had adequate evidences of validity.